Genotypic and phenotypic analysis of Salmonella enterica serovar Derby, looking for clues explaining the impairment of egg isolates to cause human disease - Traglia, German Matias; Betancor, Laura; Yim, Lucia; Iriarte, Andrés; Chabalgoity, José Alejandro (Frontiers in Microbiology, 2024)
Salmonella enterica serovar Derby causes foodborne disease (FBD) outbreaks worldwide, mainly from contaminated pork but also from chickens. During a major epidemic of FBD in Uruguay due to S. Enteritidis from poultry, we conducted a large survey of commercially available eggs, where we isolated many S. Enteritidis strains but surprisingly also a much larger number (ratio 5:1) of S. Derby strains. No single case of S. Derby infection was detected in that period, suggesting that the S. Derby egg strains were impaired for human infection.We sequenced fourteen of these egg isolates, as well as fifteen isolates from pork or human infection that were isolated in Uruguay before and after that period, and all sequenced strains had the same sequence type (ST40). Phylogenomic analysis was conducted using more than 3500 genomes from the same sequence type (ST), revealing that Uruguayan isolates clustered into four distantly related lineages. Population structure analysis (BAPS) suggested the division of the analyzed genomes into nine different BAPS1 groups, with Uruguayan strains clustering within four of them. All egg isolates clustered together as a monophyletic group and showed differences in gene content with the strains in the other clusters. Differences included variations in the composition of mobile genetic elements, such as plasmids, insertion sequences, transposons, and phages, between egg isolates and human/pork isolates. Egg isolates showed an acid susceptibility phenotype, reduced ability to reach the intestine after oral inoculation of mice, and reduced induction of SPI-2 ssaG gene, compared to human isolates from other monophyletic groups. Mice challenge experiments showed that mice infected intraperitoneally with human/pork isolates died between 1-7 days p.i., while all animals infected with the egg strain survived the challenge. Altogether, our results suggest that loss of genes functions, the insertion of phages and the absence of plasmids in egg isolates may explain why these S. Derby were not capable of producing human infection despite being at that time, the main serovar recovered from eggs countrywide.